Natural variation in growth and leaf ion homeostasis in response to salinity stress in Panicum hallii - Haque, Taslima; Bhaskara, Govinal Badiger; Yin, Jun; Bonnette, Jason; Juenger, Thomas E. (Frontiers in Plant Science, 2022)
Soil salinity can negatively impact plants growth, development and fitness. Natural plant populations restricted to coastal environments may evolve to saline habitats and provide insights into the process of salinity adaptation. We investigated the growth and physiological responses of coastal and inland populations of Panicum hallii to experimental salinity treatments. Coastal genotypes demonstrated less growth reduction and superior ion homeostasis compared to the inland genotypes, supporting a hypothesis of local adaptation. We identified several QTL associated with the plasticity of belowground biomass, leaf sodium content, potassium content and their ratio which underscores the genetic variation present in this species for salinity responses. Genome-wide transcriptome analysis in leaf and root tissue revealed tissue specific overexpression of genes including several cation transporters in the coastal genotype. These transporters mediate sodium ion compartmentalization and potassium ion retention and thus suggesting that maintenance of ionic homeostasis of coastal genotypes might be due to the regulation of these ion transporters. These findings contribute to our understanding of the genetics and molecular mechanisms of salinity adaptation in natural populations, and widen the scope for genetic manipulation of these candidate genes to design plants more resilient to climate change.